Mechanisms underlying the acute toxicity of fullerene to Daphnia magna: Energy acquisition restriction and oxidative stress - Lv, Xiaohui; Huang, Boming; Zhu, Xiaoshan; Jiang, Yuelu; Chen, Baiyang; Tao, Yi; Zhou, Jin; Cai, Zhonghua (Water research (Oxford), 2017)
The toxicity of fullerene (C60) to Daphnia magna has been a subject with increasing concerns. Nevertheless, the underlying mechanisms are still poorly understood. In the present study, we evaluated various aspects of the toxicological impacts of C60 on daphnia. After a 72-h exposure, the 50% effective concentration of C60 was 14.9 mg/L for immobilization, and 16.3 mg/L for mortality. Daphnia exhibited a quick uptake of C60 with a body burden value of 413 μg/g in wet weight in the 1 mg/L C60 treatment group. Transmission electron microscopy observations revealed that C60 had mainly accumulated in the guts of organisms. The feeding rate, gut ultra-structural alterations, and digestive enzyme activities of daphnia in response to C60 treatment were evaluated. The results revealed a significant reduction in the digestion and filtration rates, as well as gut impairment and inhibition of digestive enzymes (cellulose, amylase, trypsin, and β-galactosidase) activity of C60 exposed daphnia. In addition, the changes in superoxide dismutase (SOD) and malondialdehyde (MDA) levels in daphnia under C60 exposures were also discovered. These results, for the first time, provide systematic evidence that C60 caused a restriction in energy acquisition and increased oxidative damage in daphnia, which might be related to the bioaccumulation of C60 and finally led to the immobility and mortality. •The acute toxicity and bioaccumulation of C60 in daphnia were investigated.•C60 induced energy acquisition restriction in daphnia.•C60 mediated the production of oxidative stress in daphnia.